Angiology : Depth Classification version of CC (Classification Problems. 93) (Design Series. 51) - Seetharama, S. (Journal of Information and Knowledge, 1979)
A Depth Classification Version of Colon Classification (=CC) for compound subjects going with the Host Subject" L,3 Angiology" is given. The methodology for classification and the current version of the notational system of CC have been used. An Alphabetical Index to the schedules, a list of 22 examples classified according to the scheme for classification, and an alphabetical index to the subjects are given.